2005
DOI: 10.4049/jimmunol.175.11.7512
|View full text |Cite
|
Sign up to set email alerts
|

The Exopolysaccharide Alginate Protects Pseudomonas aeruginosa Biofilm Bacteria from IFN-γ-Mediated Macrophage Killing

Abstract: The ability of Pseudomonas aeruginosa to form biofilms and cause chronic infections in the lungs of cystic fibrosis patients is well documented. Numerous studies have revealed that P. aeruginosa biofilms are highly refractory to antibiotics. However, dramatically fewer studies have addressed P. aeruginosa biofilm resistance to the host’s immune system. In planktonic, unattached (nonbiofilm) P. aeruginosa, the exopolysaccharide alginate provides protection against a variety of host factors yet the role of algin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
314
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(326 citation statements)
references
References 54 publications
(53 reference statements)
6
314
0
6
Order By: Relevance
“…Mucoid strains of P. aeruginosa appear to have increased resistance to antibiotic therapy and innate and adaptive immune responses, but the mechanisms are not well understood. In vitro studies of murine leukocyte killing have indicated impaired survival of P. aeruginosa mutants defective in alginate synthesis relative to wild-type P. aeruginosa (including PA14) and mucoid P. aeruginosa strains (31). These data were suggestive of impaired phagocyte-mediated killing stimulated by IFN-γ and do not indicate increased resistance of mucoid strains relative to nonmucoid strains, but suggest a functional role for alginate biosynthesis in the ability of P. aeruginosa to survive phagocytemediated killing.…”
Section: Elegans Mutants Defective In Oxygen Sensation Have Enhancedmentioning
confidence: 62%
“…Mucoid strains of P. aeruginosa appear to have increased resistance to antibiotic therapy and innate and adaptive immune responses, but the mechanisms are not well understood. In vitro studies of murine leukocyte killing have indicated impaired survival of P. aeruginosa mutants defective in alginate synthesis relative to wild-type P. aeruginosa (including PA14) and mucoid P. aeruginosa strains (31). These data were suggestive of impaired phagocyte-mediated killing stimulated by IFN-γ and do not indicate increased resistance of mucoid strains relative to nonmucoid strains, but suggest a functional role for alginate biosynthesis in the ability of P. aeruginosa to survive phagocytemediated killing.…”
Section: Elegans Mutants Defective In Oxygen Sensation Have Enhancedmentioning
confidence: 62%
“…These include treatment with hydrogen peroxide, osmotic shock and oxygen limitation. 50,54,59,60,[63][64][65][66] This raises the intriguing question of whether or not the RpoE/AlgU regulon, and alginate production, are induced immediately after environmental P. aeruginosa enters the lung. Indeed, there is evidence to support this.…”
mentioning
confidence: 99%
“…Alginate facilitates biofilm formation and promotes resistance to host defenses and antibiotics. 50 The alginate biosynthesis operon is positively controlled by RpoE, which is known as AlgU (or AlgT) in P. aeruginosa. 51 A proteolytic cascade analogous to that in E. coli is triggered to degrade the antisigma factor RseA (called MucA in P. aeruginosa) when misfolded OMPs interact with its DegS homolog AlgW, and LPS interacts with it RseB homolog, MucB.…”
mentioning
confidence: 99%
“…Biofilms of mucoid P. aeruginosa strains are more tolerant to antibiotics than wild-type biofilms (10), and mucoidy has been implicated in increased tolerance to host immune responses (11).…”
mentioning
confidence: 99%